Особливості сучасного процесу ретуші фотографій - Щукіна, Л. Б.; Івах, Є. Ф. (ХНУРЕ, 2025)
This work is dedicated to the process of Adobe Photoshop retouching from both technical and practical perspectives. Retouching improves picture quality by adjusting for flaws, color correction, and texture finishing to create a professional appearance. The paper explores many of the retouching tools like Spot Healing Brush, Clone Stamp, and Frequency Separation, along with recent AI based tools like Content-Aware Fill and Neural Filters. Both manual and auto mated adjustments can be facilitated through these processes to develop a naturalized and professionalized final output.
Keywords: Adobe Photoshop; процес ретуші фотографій